Primary CIC-rearranged Gastric sarcoma: A rare diagnosis - Dhungana, Saroj; Thakur, Binay; Bhandari, Nikesh; Shrestha, Shashank; Kharel, Ashish; Neupane, Deewash (Nepalese Journal of Cancer, 2023)
Gastric sarcoma is rare, accounting for 1-3% of all gastric neoplasms. WHO has published a new classification of soft tissue tumors and a group of undifferentiated round cell sarcomas, including CIC-rearranged sarcoma has been added. CIC-rearranged sarcoma has not been reported till date. We report a case of CIC-rearranged gastric sarcoma which was managed with chemotherapy and multivisceral resection.